Comparative morphological analysis of tomato somaclones in field conditions - Akter, K T; Tasmin, S; Islam, M R; Mazumder, M N N; Akhther, N (Bangladesh Journal of Nuclear Agriculture, 2025)
The instability of in vitro cultures may cause genetic and epigenetic changes in crops called somaclonal variations. Sometimes, these changes produce beneficial effects, which can be used in breeding programs to generate new cultivars with desirable characteristics. To find out the presence of beneficial variations among in vitro regenerated plants, the current study was carried out at the Horticulture Division, Bangladesh Institute of Nuclear Agriculture (BINA). Seven somaclones from two different donor parents were evaluated in this study. The result revealed significant phenotypic diversity among the somaclones and their original cultivars, especially in character plant height, leaf morphology, flower type, fruit shape, and yield components. Findings show that, among the somaclones derived from Binatomato-11, IVRP 11.6 had the highest no. of fruit plant-1 (89) and yield plot-1 (32.16 kg), whereas IVRP 11.3 had the highest single fruit weight and the best fruit quality with the highest total soluble solids (TSS) content (5.89 % brix). On the other hand, the highest yield plot-1 (39.86 kg) was produced by IVRP 13.1, which was 3.5 times higher than parent Binatomato-13, but it was not better in any other yield-related characteristics. In order to improve tomato productivity and adaptation to changing climatic conditions, somaclonal variations can be integrated into future plant breeding techniques. Bangladesh J. Nuclear Agric., 39(1): 31-45, 2025